Changes in longevity inequality by education among OECD countries before the COVID-19 pandemic - Christopher Lübker; Fabrice Murtin (BMC, 2023)
Abstract Background Disparities in life expectancy between socioeconomic groups are one of the main challenges for health policy, and their reduction over time is an important policy objective. Methods Observational study using routinely registered data on mortality around 2011 and 2016 by sex, age, educational attainment level, and cause of death in 13 member countries of the Organization for Economic Cooperation and Development (OECD). The main outcome measures are life expectancy by education at the ages of 25 and 65 in 2011 and 2016. Results Between 2011 and 2016, the life expectancy gap has increased by 0·2 years among men and 0·3 years among women from 13 available countries. The United States recorded one the largest increases in the absolute life expectancy gap, 1·3 years for women and 1·1 years for men respectively. Conclusion Inequality in longevity has increased in over half of the countries surveyed and starkly so in the United States in a context of deteriorating health. Trial registration Not applicable.